Answer:
[tex]p(x)=(x^{2} -2x+2)(x^{2} -7)[/tex]
Step-by-step explanation:
Given that one of the zeroes is 1 - i.
Complex roots occur in pairs.
This means, if a + bi is a zero of a polynomial, then a - bi is also its zero.
Therefore, 1 + i is also a zero of the polynomial.
Factors are x - (1 - i) and x - (1 + i).
Multiply the factors.
[x - (1 - i)][x - (1 + i)] = (x - 1 + i)(x - 1 - i)
[tex]=(x-1)^{2} -i^{2}[/tex]
[tex]=(x-1)^{2} +1[/tex]
[tex]=x^{2} -2x+1+1[/tex]
[tex]=x^{2} -2x+2[/tex]
Given that one of the zeroes is [tex]\sqrt{7}[/tex].
Irrational roots occur in pairs.
This means, if an irrational number m is a zero of a polynomial, then - m is also its zero.
Therefore, [tex]-\sqrt{7}[/tex] is also a zero of the polynomial.
Factors are [tex]x-\sqrt{7}[/tex] and [tex]x+\sqrt{7}[/tex].
Multiply the factors.
[tex](x-\sqrt{7} )(x+\sqrt{7} )[/tex]
[tex]=x^{2} -\sqrt{7} ^{2}[/tex]
[tex]=x^{2} -7[/tex]
Hence, the required polynomial is [tex]p(x)=(x^{2} -2x+2)(x^{2} -7)[/tex].